2017
DOI: 10.1186/s13635-017-0067-2
|View full text |Cite
|
Sign up to set email alerts
|

VISION: a video and image dataset for source identification

Abstract: Forensic research community keeps proposing new techniques to analyze digital images and videos. However, the performance of proposed tools are usually tested on data that are far from reality in terms of resolution, source device, and processing history. Remarkably, in the latest years, portable devices became the preferred means to capture images and videos, and contents are commonly shared through social media platforms (SMPs, for example, Facebook, YouTube, etc.). These facts pose new challenges to the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
194
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(196 citation statements)
references
References 20 publications
(23 reference statements)
0
194
0
2
Order By: Relevance
“…In addition, a good performance on small regions allows one to use this approach for image forgery detection and localization, especially the critical case of small-size forgeries. In Fig.3, we show the histograms of the PRNU-based (left) and noiseprint-based (right) distances computed on the widespread VISION dataset [23] in various situations (different rows). Each subplot shows three different histograms:…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In addition, a good performance on small regions allows one to use this approach for image forgery detection and localization, especially the critical case of small-size forgeries. In Fig.3, we show the histograms of the PRNU-based (left) and noiseprint-based (right) distances computed on the widespread VISION dataset [23] in various situations (different rows). Each subplot shows three different histograms:…”
Section: Proposed Methodsmentioning
confidence: 99%
“…To evaluate the efficiency of the proposed methods, we used a public dataset (VISION) [9] which comprises native and social media videos. In the dataset, were extracted from videos using ffprobe, included in ffmpeg software.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors like Samet et al in [8] just assume that I frames are the best to be used, others like Dasara et al in [9] give equal importance to I, P and B frames, and use all video frames for fingerprint estimation. Accordingly, they reported that a low accuracy in source attribution is obtained when performed on videos re-compressed by YouTube or Whatsapp (compared to their native version).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Camera forensics has become a significant field of research for various applications such as verification query image/video pairs can be attributed to the same source camera, and verification the source of a suspicious image/video [23], [24]. To the best of our knowledge, the only work exploiting ENF for camera forensics is that of Hajj-Ahmad et al [18].…”
Section: Idle Period Estimationmentioning
confidence: 99%